Usage guides of social media: journalistic regularization and informative quality - Sanchez Gonzales, Hada M.; Méndez Muros, Sandra (Estudios sobre el Mensaje Periodístico, 2015)
This paper tackles a first diagnosis of the media bet through usage guides of social networking for journalists in the current outlook of prominence in the audience who decides what, how, when and where they consume information. The goal is focused on determining the reality and perception of the aforementioned guides in the local media of Seville and the role that the journalist plays concerning to concepts such as quality, believability and freedom of expression. We base on qualitative and quantitative techniques to carry out the document analysis, as well as the observation technique that provides the survey (selfadministered, Likerttype questionnaireinstrument). To sum it up, we observe immaturity in the development of these usage guides by Sevillian local media.